2007
DOI: 10.1002/mds.21587
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of restless legs syndrome (RLS): State-of-the-art and future directions

Abstract: Several studies demonstrated that 60% of restless legs syndrome (RLS) patients have a positive family history and it has been suggested that RLS is a highly hereditary trait. To date, several loci have been mapped but no gene has been identified yet. Phenocopies and possible nonpenetrants made it difficult to detect a common segregating haplotype within the families. Defining the exact candidate region is hampered by possible intrafamilial, allelic, and nonallelic heterogeneity. One important prerequisite for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 63 publications
3
36
0
5
Order By: Relevance
“…The involvement of a major gene, with autosomal--dominant mode of transmission is evident for early--onset RLS only; while late--onset RLS appears to be compatible with a model of free transmission (Winkelmann et al 2002). In both cases, however, there is evidence for a role of a multifactorial component, with the possibility of other genetic and non--genetic factors A and B (see Winkelmann et al 2007, for a review). The link between RLS and dopaminergic transmission is perhaps not surprising given that pharmacological treatment with drugs that increase dopamine transmission alleviate symptoms (Winkelmann et al 2007).…”
Section: Restless Legs Syndrome (Rls): Rls Is Characterised By Unpleamentioning
confidence: 98%
See 1 more Smart Citation
“…The involvement of a major gene, with autosomal--dominant mode of transmission is evident for early--onset RLS only; while late--onset RLS appears to be compatible with a model of free transmission (Winkelmann et al 2002). In both cases, however, there is evidence for a role of a multifactorial component, with the possibility of other genetic and non--genetic factors A and B (see Winkelmann et al 2007, for a review). The link between RLS and dopaminergic transmission is perhaps not surprising given that pharmacological treatment with drugs that increase dopamine transmission alleviate symptoms (Winkelmann et al 2007).…”
Section: Restless Legs Syndrome (Rls): Rls Is Characterised By Unpleamentioning
confidence: 98%
“…In both cases, however, there is evidence for a role of a multifactorial component, with the possibility of other genetic and non--genetic factors A and B (see Winkelmann et al 2007, for a review). The link between RLS and dopaminergic transmission is perhaps not surprising given that pharmacological treatment with drugs that increase dopamine transmission alleviate symptoms (Winkelmann et al 2007). …”
Section: Restless Legs Syndrome (Rls): Rls Is Characterised By Unpleamentioning
confidence: 99%
“…Several studies demonstrated that 50% of restless legs syndrome (RLS) patients have a positive family history and it has been suggested that RLS is a highly hereditary trait. Linkage analysis uncovered fi ve loci based on recessive (RLS1) or dominant inher itance (RLS2-RLS5) (Winkelmann et al 2007a), a recent genome-wide reported signifi cant associ ations between RLS and three genes (Winkelmann et al 2007b). Another group has discovered a variant associated with susceptibility to periodic limb movements in sleep, which was also inversely correlated with iron stores (Stefansson et al 2007).…”
Section: Population and Samplingmentioning
confidence: 99%
“…There are several risk alleles found for RLS [13]. Variants in MEIS1, BTBD9, MAP2K5 / SKOR1, PTPRD, and TOX3 are associated with a significantly increased risk for RLS [13][14][15][16][17]. These alleles are in non-coding regions of the genes, and the metabolic pathways through which they confer the increased risk is only now being investigated.…”
Section: Introductionmentioning
confidence: 99%